Odpowiedź :
a) 12a - (-5a + 3) + 7 (2 + a) = 12a + 5a - 3 + 14 + 7a = 24a + 11
b) –4(x - y) – 3y - 2(-y - x) + 1 = -4x + 4y - 3y + 2y + 2x + 1 = -2x + 3y + 1
c) 3 - [2 + (a + 4) – 2a] · 5 = 3 - (2 + a + 4 - 2a) · 5 = 3 - (10 + 5a + 20 - 10a) = 3 - 10 - 5a - 20 + 10a = 5a - 27
d) 10a (6a + 1) + 7(6 – a) = 60a² + 10a + 42 - 7a = 60a² + 3a + 42
e) 5(+ y) - 9y - 4(y – r) + 2 = 5y - 9y - 4y + 4r = 4r - 8y
Odpowiedź:
a) 12a - (-5a + 3) + 7 (2 + a) = 12a+5a+3+14+7a = 24a+17
b) –4(x - y) – 3y - 2 (-y- x) + 1 = -4x+4y-3y+2y+2x = -2x+3y
c) 3 - [2 + (a + 4) – 2a) • 5 = 3-2-a+4+2a*5 = 11a+5
d) 10a (6a + 1) + 7 (6 – a) = 60a^2+10a+42-7a = 60a^2+3a+42
e) 5(+ y) - 9y - 4(y – r) +2 = -4y-4y+4r+2 = 4r-8y+2
wydaje mi się że jest dobrze
liczę na naj